PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PERANGKAT DESA MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA KANTOR DESA KECAMATAN BANYUPUTIH KABUPATEN SITUBONDO - Failin, Isma Nur; Hamdun, Edy Kusnadi; Ariyantiningsih, Febri (Fakultas Ekonomi dan Bisnis, 2023)
A village administration office is a building or room used as the administrative center of village-level government. The village administration office serves as a gathering place for village officials, including the head of the village, village administrative staff, and various sections or units related to public services and the interests of the village community. This study aims to investigate the effect of work discipline and work motivation on the performance of village officials in Banyuputih District, Situbondo Regency. This study aims to determine whether job satisfaction correlates with the relationship between work discipline and work motivation that affects the performance of village officials. The population in this study was village officials in Banyuputih District. The sampling technique used saturated sampling. This study's data analysis and hypothesis testing used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS 3.0 application show that work discipline has a negative but insignificant effect on job satisfaction, work discipline is not proven to have a significant effect on performance, work motivation has a significant effect on job satisfaction, work motivation has a significant effect on performance, job satisfaction has a significant effect on performance. The results of the indirect effect hypothesis test showa that the variable work discipline on performance through job satisfaction has a negative but insignificant effect; work motivation on performance through job satisfaction is not proven to have a significant effect.